INVESTIGATING THE IMPACT OF INTERNATIONAL FINANCIAL REPORTING STANDARDS ON GLOBAL FINANCIAL TRANSPARENCY - Nida Garnida Fitrianti; Nia Ria; Raden Roro Fatmasari (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background:The global financial landscape is increasingly interconnected, and the need for transparent and comparable financial reporting across borders is critical. The International Financial Reporting Standards (IFRS) have been introduced to address these needs, aiming to harmonize accounting practices worldwide. This research explores the impact of IFRS on global financial transparency, focusing on how its adoption affects the quality of financial reporting, comparability, and investor confidence across various regions and industries. Aims:The primary aim of this study is to assess the influence of IFRS adoption on financial transparency in multinational corporations. The research aims to investigate the effect of IFRS on financial statement accuracy, transparency in financial reporting, and the role it plays in improving global financial integration. Research Method:This paper adopts a qualitative research method, combining literature review with case studies from various regions that have adopted IFRS. A comparative analysis is conducted to examine the changes in financial transparency pre- and post-IFRS adoption in countries such as the European Union, the United States, and emerging economies. Results and Conclusion:The research reveals that IFRS adoption has led to significant improvements in financial transparency, particularly in terms of comparability and consistency of financial statements across borders. However, challenges remain in terms of full compliance, especially in emerging economies. The study concludes that while IFRS has positively impacted global financial transparency, further efforts are needed to standardize its implementation worldwide. Contribution:This study contributes to the ongoing discourse on global financial standards by providing empirical evidence on the effect of IFRS on financial transparency. The findings offer insights for regulators, financial institutions, and multinational corporations seeking to understand the implications of IFRS adoption.